INOVASI PELAYANAN PUBLIK DI ERA NEW NORMAL : (Studi tentang Transformasi Pelayanan SINANTI (Sistem Pelayanan Perizinan Terintegrasi) di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja (DPMPTSP & NAKER) Kabupaten Sumenep) - Apriliya, Annisak (Jurnal Administrasi Publik, 2023)
Public Service Innovation in the New Normal Era (A Study on the Transformation of SINANTI (Integrated Licensing Service System) in the One-Stop Integrated Services and Manpower Office (DPMPTSP & NAKER) of Sumenep Regency). DPMPTSP & NAKER of Sumenep Regency has felt the impact of Covid-19 during the pandemic, including in providing Outdoor Advertising / Media Permit services. To facilitate the public in granting permits, DPMPTSP & NAKER of Sumenep Regency innovated by creating a system called SIPEKAT (Fast Service Information System), which was later renamed SINANTI (Integrated Licensing Service System) during the evaluation process. SINANTI is directly integrated with the taxpayer system on the server of the Revenue Management and Financial and Asset Management Agency (BPPKAD) of Sumenep Regency, specifically the e-PAD application. The formation of SINANTI originated from the discovery of a significant discrepancy between the number of advertising tax assessment letters issued by BPPKAD of Sumenep Regency and the number of advertising permits issued by DPMPTSP & NAKER of Sumenep Regency. The aim of this research is to describe and analyze the innovation process carried out by DPMPTSP & NAKER of Sumenep Regency and to describe and analyze the factors that drive and hinder the implementation of public service innovation in DPMPTSP & NAKER of Sumenep Regency. The research method used is descriptive research using a qualitative approach.